The frequency of 844ins68 mutation in the cystathionine β-synthase gene is not increased in patients with venous thrombosis - Franco, Rendrik; Maffei, Francisco Humberto de Abreu [UNESP]; Lourenço, Dayse; Piccinato, Carlos; Morelli, Vânia; Thomazini, Isolete [UNESP]; Zago, Marco (My University, 1998)
Background and Objectives. A frequent mutation in the cystathionine β- synthase (CBS) gene (844ins68, a 68-bp insertion in the coding region of exon 8) was recently discovered. In the present study we investigated this mutation as a candidate risk factor for venous thrombosis. Design and Methods. The prevalence of the 844ins68 CBS mutation was determined in 101 patients with objectively diagnosed deep venous thrombosis and in 101 healthy controls matched for age, sex and race. PCR amplification of a DNA fragment containing exon 8 of the CBS gene was employed to determine the genotypes. Additionally, Bsrl restriction enzyme digestion of the PCR products was performed in all samples from carriers of the insertion, to test for concurrent presence of a second mutation (T833C) in the CBS gene. Results. The insertion was found in 21 out of 101 patients (20.8%; allele frequency 0.109) and in 20 out of 101 controls (19.8%; allele frequency 0.114), yielding a relative risk for venous thrombosis related to the 844ins68 CBS mutation close to 1.0. In addition, the T833C CBS mutation was detected in all alleles carrying the 844ins68 CBS insertion, confirming the co- inheritance of the two mutations. Interpretation and Conclusions. Our findings do not support the hypothesis that the 844ins68 mutation in the CBS gene is a genetic risk factor for venous thrombosis.
Keywords: Cystathionine β-synthase; Homocysteine; Insertion variant; Mutation; Venous thrombosis; adolescent; adult; allele; amino acid metabolism; child; controlled study; enzyme activity; exon; female; gene frequency; gene insertion; gene mutation; genetic risk; genotype; heterozygosity; homozygosity; human; major clinical study; male; polymerase chain reaction; prevalence; vein thrombosis; Adolescent; Adult; Alleles; Amino Acid Substitution; Brazil; Child; Child, Preschool; Codon; Cystathionine beta-Synthase; DNA Mutational Analysis; Exons; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Infant; Male; Middle Aged; Mutagenesis, Insertional; Point Mutation; Polymerase Chain Reaction; Risk Factors; Thrombophilia; Venous Thrombosis